A complementary electrochromic device with highly improved performance based on brick-like hydrated tungsten trioxide film - Jiao, Zhihui (2013)
Uniform and well adhesive nanostructured hydrated tungsten trioxide (3WO3·H2O) films were grown on fluorine doped tin oxide (FTO) substrate via a facile and template-free crystal-seed-assisted hydrothermal method by addition of ammonium sulfate ((NH4)2SO4) and hydrogen peroxide (H2O2). X-ray diffraction (XRD) studies indicated that the films are of orthorhombic structure. Scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM) analysis showed that the film was composed of brick-like nanostructures with a preferred growing direction along (002). The influence of seed layer, (NH4)2SO4 and H2O2 on the products were also studied. The film showed good cyclic stability, comparable switching speed and coloration efficiency (30.1 cm2 C−1). A complementary electrochromic device based on the film and Prussian blue depicted highly improved color contrast, coloration/ bleaching response (1.8 and 3.7 s respectively) and coloration efficiency (164.6 cm2 C−1).